Indirect rule: armed groups and customary chiefs in eastern DRC - Soeren J. Henn; Gauthier Marchais; Christian M. Mugaruka; Raul Sanchez de la Sierra (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This paper leverages a novel panel dataset covering the histories of 306 chiefs and 256 episodes of village governance and taxation by armed groups in 106 villages in eastern Democratic Republic of the Congo in order to analyse the relationship between the governance of armed groups and the power of rural chiefs. The paper devises a strategy to measure chiefs' power, as well as the governance and taxation arrangements established by armed groups along several dimensions. We find that, when chiefs are powerful, armed groups are less likely to adopt direct rule and more likely to adopt indirect rule governance arrangements. We also find that the use of direct rule increases with an armed group's tenure.
Keywords: 330; violent conflict; elite control; political economy